2012
DOI: 10.1017/s0031182011002095
|View full text |Cite
|
Sign up to set email alerts
|

Do the level of energy reserves, hydration status andBorreliainfection influence walking byIxodes ricinus(Acari: Ixodidae) ticks?

Abstract: Ixodes ricinus horizontal movement within a humidity gradient and the influence of infection by Borrelia burgdorferi sensu lato (s.l.) on tick walking were investigated. Nymphs were placed within an arena containing a humidity gradient ranging from 45 to 95% relative humidity (RH). After 1 h of acclimation at 70% RH ticks were released so that they could either stay, or walk towards either the wet or the dry end. Their position was recorded 2 h post-release. Fat content was quantified and Borrelia infection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 43 publications
(96 reference statements)
5
50
0
Order By: Relevance
“…I. ricinus nymphal ticks were sampled from the Bois de l'Hôpital site in a deciduous forest near Neuchâtel (47°00=55.6ЉN, 6°94=16.7ЉE; surface area of 1 ha) over a period of 3 years (2009 to 2011). These ticks were sampled as part of the PhD thesis of Coralie Herrmann, and details of the field sampling and subsequent molecular methods have been described previously (27,(78)(79)(80)(81).…”
Section: Methodsmentioning
confidence: 99%
“…I. ricinus nymphal ticks were sampled from the Bois de l'Hôpital site in a deciduous forest near Neuchâtel (47°00=55.6ЉN, 6°94=16.7ЉE; surface area of 1 ha) over a period of 3 years (2009 to 2011). These ticks were sampled as part of the PhD thesis of Coralie Herrmann, and details of the field sampling and subsequent molecular methods have been described previously (27,(78)(79)(80)(81).…”
Section: Methodsmentioning
confidence: 99%
“…The present study is a meta-analysis of seven independent sampling occasions that were conducted by Coralie Herrmann over the course of her Ph.D. thesis (35)(36)(37)(38). The ticks collected on these sampling occasions were used in studies to quantify fat content in ticks and to test how temperature, humidity, and Borrelia infection influenced the physiology, behavior, and survival of I. ricinus nymphs (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The sampling site was a mixed forest situated 600 m above sea level on the south-facing slope of Chaumont Mountain, Neuchâtel, Switzerland (47°00= N, 6°57= E). Field sampling of questing ticks and subsequent molecular methods have been described in detail elsewhere (35,(36)(37)(38). Briefly, our molecular protocol consisted of two successive steps: (i) quantitative PCR (qPCR) to identify Borrelia-infected nymphs and to estimate the spirochete load, and (ii) reverse line blot (RLB) of the Borrelia-infected nymphs to identify the Borrelia genospecies.…”
Section: Methodsmentioning
confidence: 99%
“…While the differences among species and with surface incline were not unexpected, the signiÞcant differences in tick motility among endosymbiont infection classes represents a novel result. A few previous studies examined the effect of B. burgdorferi infection on motility of Ixodes ticks (Lefcort and Durden 1996, Herrmann and Gern 2012. Here, the microbes are vertically-transmitted (transovarial) symbionts and we found that infection both increased (Rickettsia) and decreased (Arsenophonus) motility relative to uninfected ticks depending on tick species and incline.…”
Section: Discussionmentioning
confidence: 67%
“…For example, Lefcort and Durden (1996) found that B. burgdorferi infection signiÞcantly decreased activity of adult I. scapularis Say relative to uninfected ticks, but infected nymphs exhibited an opposite trend. Likewise, Herrmann and Gern (2012) found that Borrelia infection reduced walking activity of infected, high-fat I. ricinus L. nymphs but there was no difference in low-fat nymphs. also reported that B. burgdorferi infection decreased locomotive activity of both adult and immature I. ricinus ticks.…”
mentioning
confidence: 92%